Genetic variability of the sws1 cone opsin gene among New World monkeys. Issue 12 (29th September 2020) - Mantovani, Viviani; Hauzman, Einat; Corredor, Vitor H.; Goulart, Paulo R. K.; Galvão, Olavo; Talebi, Mauricio; Pessoa, Daniel M. A.; Soares, Juliana G. M.; Fiorani, Mario; Gattass, Ricardo; Fix Ventura, Dora; Bonci, Daniela M. O.
Abstract: Vision is a major sense for Primates and the ability to perceive colors has great importance for the species ecology and behavior. Visual processing begins with the activation of the visual opsins in the retina, and the spectral absorption peaks are highly variable among species. In most Primates, LWS/MWS opsins are responsible for sensitivity to long/middle wavelengths within the visible light spectrum, and SWS1 opsins provide sensitivity to short wavelengths, in the violet region of the spectrum. In this study, we aimed to investigate the genetic variation on the sws1 opsin gene of New World monkeys (NWM) and search for amino acid substitutions that might be associated with the different color vision phenotypes described for a few species. We sequenced the exon 1 of the sws1 opsin gene of seven species from the families Callitrichidae, Cebidae, and Atelidae, and searched for variation at the spectral tuning sites 46, 49, 52, 86, 90, 93, 114, 116, and 118. Among the known spectral tuning sites, only residue 114 was variable. To investigate whether other residues have a functional role in the SWS1 absorption peak, we performed computational modeling of wild‐type SWS1 and mutants A50I and A50V, found naturally among the species investigated. Although in silico analysis did not show any visible effect caused by these substitutions, it is possible that interactions of residue 50 with other sites might have some effect in the spectral shifts in the order of 14 nm, found among the NWM. We also performed phylogenetic reconstruction of the sws1 gene, which partially recovered the species phylogeny. Further studies will be important to uncover the mutations responsible for the phenotypic variability of the SWS1 of NWM, and how spectral tuning may be associated with specific ecological features such as preferred food items and habitat use. Abstract : Spectral variability of sws1 opsin gene in humans and New World monkeys. Highlights: Spectral tuning sites of the SWS1 opsin are conserved among New World monkeys, with the exception of residue 114. Interactions among other unknown spectral tuning sites may also play a role in the spectral shifts of the SWS1 opsins of Primates. Spectral shifts of the violet‐sensitive opsins of New World monkeys might be associated with ecological features such as variations in the preferred food items and habitat selection.